The Emergence of Scientific Literacy in Science E-Module Learning Devices - Rizky Nafaida; Ekariana S. Pandia; Dini Fitria; Nursamsu Nursamsu; Nurhasnah Manurung (Postgraduate, University of Mataram, 2023)
Learning tools need to be implemented in today's learning innovations. Currently the government is implementing a new curriculum with a new policy in the form of scientific literacy learning. This learning focuses on daily problem-solving activities related to natural science. Therefore, there is a need for teacher innovation in developing E-Module teaching materials as a form of modern learning application. The purpose of this study was to determine the emergence of scientific literacy in science e-module learning tools. The method in this research using descriptive method. The results of this study indicate that the e-module used by teachers is related to content aspects worth 84% which is stated as good, process aspects with a percentage worth 78% stated well and in terms of context with a percentage of 81%. related to the emergence of scientific literacy while the results of interviews with science teachers indicated that the science e-module learning tools used had scientific literacy in each science material